Poly(hydroxylauric acid maleate-co-sebacic anhydride) synthesis, characterization, in vitro degradation and drug release behavior - Dagbay, Kevin Buadlart; Sumera, Florentino C. (Quezon City Institute of Chemistry, College of Science, University of the Philippines Diliman, 2009)
A new class of fatty acid-based poly(ester-anhydride) with drug releasing behavior was synthesized from hydroxylauric acid maleate (HOLAM) and sebacic acid (SA). Thus (HOLA) with maleic anhydride where mixed HOLA was prepared by reacting lauric acid with 30% hydrogen peroxide in trifluoroacetic acid. The poly(ester-anhydrides) of HOLAM and SA were then synthesized by melt polycondensation to yield polymers with molecular weights of 47,000 to 240,000 g/mol as determined by GPC and yields ranging from 55 to 75%.
Thesis (Master of Science in Chemistry)-- University of the Philippines Diliman
Keywords: Fatty acids -- Synthesis